2016
DOI: 10.1016/j.gene.2016.06.063
|View full text |Cite
|
Sign up to set email alerts
|

The synovial microenvironment of osteoarthritic joints alters RNA-seq expression profiles of human primary articular chondrocytes

Abstract: Osteoarthritis (OA) is a disabling degenerative joint disease that prompts pain with limited treatment options. To permit early diagnosis and treatment of OA, a high resolution mechanistic understanding of human chondrocytes in normal and diseased states is necessary. In this study, we assessed the biological effects of OA-related changes in the synovial microenvironment on chondrocytes embedded within anatomically intact cartilage from joints with different pathological grades by next generation RNA-sequencin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 51 publications
1
18
0
Order By: Relevance
“…However, RNA-seq has the unique ability to determine the relative expression levels of all genes within a cell or tissue. This technique has not yet been widely used on articular cartilage, [8][9][10][11][12][13][14] and to the best of our knowledge, the transcriptome-wide profile of articular cartilage obtained from healthy knee joints has not been reported.…”
mentioning
confidence: 99%
“…However, RNA-seq has the unique ability to determine the relative expression levels of all genes within a cell or tissue. This technique has not yet been widely used on articular cartilage, [8][9][10][11][12][13][14] and to the best of our knowledge, the transcriptome-wide profile of articular cartilage obtained from healthy knee joints has not been reported.…”
mentioning
confidence: 99%
“…Furthermore, considering alginate beads model, we demonstrated that GAGs production was significantly higher in NC cultures compared to ACs and we conducted the cell culture until obtaining a quantifiable cartilage matrix (seven weeks). Different authors confirmed that NCs show superior and more reproducible in vitro chondrogenic potential [7,18,19,20]; this is possibly due to the pathological condition of articular tissues that are commonly harvested in patients with osteoarthritis or after sport trauma (during joint replacement surgery) [21,22]. These patients were typically treated with cortisone and other anti-inflammatory drugs, which are able to partially suppress the inflammatory cascade but, at the same time, could have an inhibition effect on articular chondrocyte proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Because human adipose tissue is a readily accessible source of such multipotent adult stem cells, human adipose‐deriveds MSCs have been well characterized and are being considered for stem cell treatments of musculoskeletal tissues disorders . Our research group has extensively studied a number of joint and cartilage disorders that could benefit from MSC therapy as well as examined environmental factors that may impact the effective therapeutic dose of stem cells …”
Section: Introductionmentioning
confidence: 99%
“…18,19 Because human adipose tissue is a readily accessible source of such multipotent adult stem cells, human adipose-deriveds MSCs have been well characterized and are being considered for stem cell treatments of musculoskeletal tissues disorders. 20,21 Our research group has extensively studied a number of joint and cartilage disorders that could benefit from MSC therapy [22][23][24][25][26][27] as well as examined environmental factors that may impact the effective therapeutic dose of stem cells. [28][29][30][31][32][33][34] Injected local anesthetics are commonly applied for both diagnostic and therapeutic purposes in perioperative and ambulatory settings in orthopedic practices 35 and for the treatment of musculoskeletal pain.…”
Section: Introductionmentioning
confidence: 99%